Change laboratory as a tool to address moral-ethical tensions in the work of early childhood education professionals - Lasse Lipponen; Rajala, Antti; Jaakko Hilppö; Annukka Pursi (My University, 2024)
Our study contributes to research on moral-ethical tensions in the work of early childhood educators by applying cultural-historical activity theory, and Change Laboratory (CL) intervention. We argue that studying and resolving moral-ethical tensions cannot be done without addressing the underlying contradictions which pertain to particular cultural-historical context and local practices. This requires a shift of focus from individual educators’ perspective to the whole system of their collaborative activity. In result, we identify two historical developments which produce the moral-ethical tensions in educators' work, and we explore how the educators invented expansive solutions to address these tensions in the CL sessions.